Association between Plasma Protein C Activity and Adverse Pregnancy Outcome in Pregnant Women: A Retrospective Cohort Study - Yunxia Wang; Xiaoli Wang; Jian Xu; Xiaojing Zhang; Shan Wang (Clinical and Experimental Obstetrics & Gynecology, 2023)
Background: To assess the variations in protein C (PC) activity throughout pregnancy and investigate potential correlations between plasma PC activities and adverse pregnancy outcomes. Methods: A retrospective cohort study was conducted among 1511 women who underwent PC activity testing at a hospital in China from June 2011 to August 2021. t-test, Kruskal Wallis, Fisher’s exact test, logistic regression and receiver operator characteristic (ROC) analysis were used for analysis of data. Results: The PC activity demonstrated a significant increase during the second trimester of pregnancy. The PC activity was found to be lower in pregnant women with a history of thrombosis (median, 95.70% [interquartile range (IQR), 85.50–114.60%]) as compared to those without (median, 109.00% [IQR, 95.00–124.60%], p = 0.008) or with current thrombosis (median, 101.10% [IQR, 85.30–117.00%]) compared to those without such events (median, 109.00% [IQR, 95.00–124.78%], p = 0.013). History of thrombosis was the independent risk factor of current thrombosis during pregnancy (odd ratio (OR) 260.57; 95% confidence interval (95% CI), 76.751–884.689; p < 0.001). The PC activity of 125 cases of threatened abortion was significantly lower than that of asymptomatic women (median, 100.80% [IQR, 91.30–113.15%] vs median, 110.00% [IQR, 95.65–125.00%], p < 0.001). Multivariate analysis showed that the low PC activity (OR 0.985; 95% CI, 0.976–0.994, p = 0.001), gestational age (OR 0.960; 95% CI, 0.946–0.975; p < 0.001) and hypothyroidism (OR 1.888; 95% CI, 1.054–3.381; p < 0.05) were risk factors for threatened abortion. There was no difference in PC activity between fetal loss, hypertensive disorder complicating pregnancy (HDCP), fetal growth restriction (FGR), oligohydramnios, placental abruption and those without. Conclusions: Women with a history of thrombosis and decreased PC activity are risk factors for thrombosis and threatened abortion during pregnancy, respectively. However, no significant correlation was observed between PC activity and fetal loss, HDCP, FGR, oligohydramnios or placental abruption.